2011
DOI: 10.4162/nrp.2011.5.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Zinc status and growth of Korean infants fed human milk, casein-based, or soy-based formula: three-year longitudinal study

Abstract: To evaluate the effect of feeding methods on growth and zinc nutritional status of infants early in life, we monitored from birth to 36 months in 51 infants who were exclusively fed human milk (HM, n = 20), casein-based formula (CBF, n = 12), or soy-based formula (SBF, n = 19) during the first five months of life. Zinc status was assessed by analyzing serum zinc concentrations and zinc intakes. Zinc contents in HM and formulas were measured. Zinc intake was estimated by weighing infants before and after feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 25 publications
(21 reference statements)
2
20
0
3
Order By: Relevance
“…This leads to daily zinc intakes of around 3 to 5 mg. Such levels of intake were not found to be associated with zinc deficiency in a study in Korean infants who received daily around 4 to 4.5 mg zinc from cow's milk-based formulae or around 5.5 to 7 mg zinc from soy-based formulae (Han et al, 2011). 6 to < 12 months Breast milk does not provide sufficient amounts of zinc for infants older than six months (Prasad, 2003). In addition to breast milk, age-appropriate foods should be consumed in order to meet requirements (Krebs et al, 2012).…”
Section: To < 6 Monthsmentioning
confidence: 94%
“…This leads to daily zinc intakes of around 3 to 5 mg. Such levels of intake were not found to be associated with zinc deficiency in a study in Korean infants who received daily around 4 to 4.5 mg zinc from cow's milk-based formulae or around 5.5 to 7 mg zinc from soy-based formulae (Han et al, 2011). 6 to < 12 months Breast milk does not provide sufficient amounts of zinc for infants older than six months (Prasad, 2003). In addition to breast milk, age-appropriate foods should be consumed in order to meet requirements (Krebs et al, 2012).…”
Section: To < 6 Monthsmentioning
confidence: 94%
“…Suboptimal zinc status has frequently been reported in studies of young children from high-income countries, including New Zealand [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Inadequate zinc status during early childhood is associated with an increased risk of infection [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the micronutrient contents of human milk in Korea were performed in the 1980s and 1990s [ 9 10 11 ] and involved only small sample sizes. Han et al [ 12 ] reported changes in zinc concentrations during lactation, and other investigators have reported increased incidences of anemia and vitamin D deficiency among breastfed infants due to low iron and vitamin D levels in breast milk [ 13 14 15 16 17 ].…”
Section: Introductionmentioning
confidence: 99%